Speaking a foreign language and its effect on F0. (July 2013) - Järvinen, Kati; Laukkanen, Anne-Maria; Aaltonen, Olli
Abstract This study investigated whether speaking a foreign language affects the fundamental frequency (F0) of speech in 16 native Finnish and 14 native English subjects reading a text in Finnish and in English. The speech samples were analyzed for the mean and range of F0. Speaking a foreign language caused a change in F0 for the Finnish subjects, while the result was not as unambiguous for the English subjects. The change in F0 may be a result of adaptation to a certain pitch level in the foreign environment. Experience in using the foreign language did not show significant correlation to the change in F0, which suggests either individual differences in sensitivity to adaptation or difficulty in quantifying the amount of experience.